Characteristics of patients with low back and leg pain seeking treatment in primary care: baseline results from the ATLAS cohort study. Issue 1 (December 2015) - Konstantinou, Kika; Dunn, Kate; Ogollah, Reuben; Vogel, Steven; Hay, Elaine
Abstract Background Patients with back pain radiating to the leg(s) report worse symptoms and poorer recovery than those with back pain alone. Robust evidence regarding their epidemiological profile is lacking from primary care, the setting where most of these patients will present and be managed. Our objective was to describe the characteristics of patients with back and leg pain, including sciatica, seeking treatment in primary care. Methods Adults visiting their general practitioner with back and leg pain, of any duration and severity, were invited to participate. Participants completed questionnaires, underwent clinical assessments and received MRI scans. Characteristics of the sample are described, and differences between patients diagnosed with referred leg pain and those with sciatica are analysed. Results Six hundred nine patients participated; 62.6 % were female, mean (SD) age 50.2 (13.9). 67.5 % reported pain below the knee, 60.7 % were in paid employment with 39.7 % reporting time off work. Mean disability (RMDQ) was 12.7 (5.7) and mean pain intensity was 5.6 (2.2) and 5.2 (2.4) for back and leg respectively. Mean sciatica bothersomeness index (SBI) was 14.9 (5.1). Three quarters (74.2 %) were clinically diagnosed as having sciatica. In the sciatica group, leg pain intensity, neuropathic pain, pain below the knee, leg pain worse than back pain, SBI and positive MRI findings were significantly higher as compared to patients with referred leg pain. Conclusions This primary care cohort reported high levels of disability and pain. This is the first epidemiological study of unselected primary care patients seeking healthcare for back and leg pain. Follow-up of this cohort will investigate the prognostic value of their baseline characteristics. This new information will contribute to our understanding of the characteristics and clinical features of this population, and will underpin future research aimed at defining prognostic subgroups to enable better targeting of health care provision.